Pediococcus acidilactici as a potential probiotic to be used in food industry - Barbosa, Joana (2016)
The objective of this study was to compare the results obtained between a commercial probiotic bacterium and a strain of Pediococcus acidilactici isolated from a food matrix. Besides the characterisation of the isolates, the main focus of this work was to evaluate their ability to survive through simulated gastrointestinal tract passage as well as the effect of the spray drying process to be used as concentrated cultures in the food industry. Both lactic acid bacteria produced any of the virulence determinants investigated; they exhibited no significant antibiotic resistances and <1logunit reduction in viable counts was obtained after exposure to simulated gastrointestinal tract conditions. Concentrated cultures of P.acidilactici HA-6111-2 in 10% (w/v) of reconstituted skim milk were obtained by spray drying and, after 60days of storage at 4 degrees C, <1logunit reduction in viable count was recorded. In conclusion, from these preliminary characterisation tests and its extended viability in the dried form, this P.acidilactici strain should be considered as a potentially useful probiotic.